MISUSE OF THE SARDINE FISH CRACKERS BRAND WITHOUT THE BUSINESS OWNER'S PERMISSION IN TEMBUNG VILLAGE, DSN FACT PERSPECTIVE NUMBER 1/MUNAS/VII/5/2005 - Intan Nabillah Erwin; Annisa Sativa (Program Pascasarjana UIN Sumatera Utara, 2025)
Brands are an important part of Intellectual Property Rights (IPR) that function not only as product identity, but also as a strategic instrument in marketing and legal protection. This study examines the practice of unauthorized misuse of the “Sardine Fish Crackers” brand in Tembung Village, Medan, and assesses its legal accountability from the perspective of Law Number 20 of 2016 and the DSN MUI Fatwa Number 1/MUNAS/VII/2005. The research method used is empirical juridical through interviews with business actors and analysis of related legal documents. The results of the study indicate that brand misuse occurs due to low legal literacy, cost and time constraints in brand registration, weak supervision, and the motive of instant profit. From a positive legal perspective, this action violates the exclusive rights of brand owners and can result in civil and criminal sanctions. Meanwhile, from an Islamic legal perspective, this action is categorized as unjust and haram because it violates the principle of property rights protection (huquq maliyyah). This research emphasizes the urgency of increasing legal awareness, enforcing regulations, and educating small business owners so that trademark abuse practices can be prevented and a fair and ethical business climate can be realized.